Uji Formulasi dan Uji Hedonik Snack Bar “GlycoBite” Berbahan Dasar Tomat dan Kacang Merah sebagai Camilan Sehat Penderita DM: Formulation Test and Hedonic Test of Snack Bars Made from Tomatoes and Red Beans as Healthy Snacks for DM Patients - Anugrah, Riva Mustika; Muntamah , Ummu; Isnawati , Setya Indah; Anisa Puspitasari; Novi Nabila Sabrinasari (JURNAL GIZI DAN KESEHATAN, 2025)
Snack bars are a practical and nutritious food product innovation. Snack bars can be formulated from a variety of local ingredients such as tomatoes, which are a source of lycopene and antoxidants, and red beans, which are rich in vegetable protein and fiber.  The healthy snack bar innovation GlycoBite is a healthy snack based on local food ingredients for patients with diabetes mellitus (DM). This study aims to determine the level of preference and nutritional content of GlycoBite snack bars made from red beans and tomatoes. This experimental study was conducted on nine formulations (F1–F9) with variations in the suppliers of tomato and red bean raw materials. Each formulation was tested for its nutritional content (energy, protein, fat, carbohydrates, fiber, antioxidant activity) used the gravimetric method and underwent a preference test covering color, aroma, texture, and taste using trained panelists (n=20). Data analysis used the Kruskal–Wallis test followed by the Mann–Whitney test (α=0.05). The results showed that the energy content of GlycoBite ranged from 279 to 295 kcal/100 g, protein from 6.7 to 9.0 g/100 g, fiber >15 g/100 g, and antioxidant activity >485 μg/mL. Significant differences (p<0.05) were found in protein content (highest in F7 = 9.02 g/100 g) and hedonic scores. The F7 formulation obtained the highest scores for taste (4.64), texture (4.14), aroma (4.31), and color (4.23). The conclusion of this study is that formulation F7 (60% tomatoes from Semarang Regency and 40% red beans from Temanggung) is the formulation   ABSTRAK Snack bar merupakan salah satu bentuk inovasi produk pangan yang praktis dan  bergizi . Snack bar merupakan produk yag dapat diformulasikan dari beragam bahan lokal seperti tomat sebagai sumber likopen dan antioksidan serta kacang merah yang kaya protein nabati dan serat.  Inovasi snack bar sehat  GlycoBite sebagai camilan sehat berbasis bahan pangan local untuk pasien Diabetes Mellitus (DM).  Penelitian ini bertujuan untuk mengetahui Tingkat kesukaan dan Kandungan zat gizi snack bar GlycoBite berbahan dasar kacang merah dan tomat. Penelitian eksperimental ini dilakukan pada 9 formulasi (F1–F9) dengan variasi pemasok bahan baku tomat dan kacang merah. Setiap formulasi diuji kandungan gizinya (energi, protein, lemak, karbohidrat, serat, aktivitas antioksidan) dengan metoda gravimetri serta dilakukan uji kesukaan yang meliputi warna, aroma, tekstur, dan rasa menggunakan panelis terlatih (n=20). Analisis data menggunakan uji Kruskal–Wallis dilanjutkan uji Mann–Whitney (α=0,05). Hasil penelitian menunjukkan bahwa kandungan energi  GlycoBite antara 279–295 kkal/100 g, protein 6,7–9,0 g/100 g, serat >15 g/100 g, dan aktivitas antioksidan >485 μg/mL. Perbedaan signifikan (p<0,05) ditemukan pada kadar protein (tertinggi F7 = 9,02 g/100 g) dan skor hedonik. Formulasi F7 memperoleh skor tertinggi untuk rasa (4,64), tekstur (4,14), aroma (4,31), dan warna (4,23). Simpulan dari penelitian ini formulasi F7 (60% tomat Kabupaten Semarang dan 40% kacang merah Temanggung) merupakan formulasi yang sesuai dengan syarat cemilan untuk DM .